Future anxiety and Problem-Solving Skills as Predictors of Suicidal Ideation among Female University Students - Al-Mufyid, Raghad Saleh; Al-Homaidhi, Ahmed Ali (Journal of Educational and Psychological Sciences, 2023)
The current study aims to identify some of the factors that would predict the occurrence of suicidal ideations by examining its relations with the variables of problem-solving skill and future anxiety among a sample of (146) of undergraduate females that aged (18 – 25) in Taif University which was collected randomly. To test the hypotheses, the study takes the correlational descriptive method using the Future Anxiety Scale (Al-Mashikhi, 2009), the Suicidal Ideation Scale (Al-Harithi, 2019), and the Problem-Solving Scale (Al-Hariri, 2017). Also, Data was analyzed statistically using Spearman’s rank correlation coefficient, multiple linear regression, means and standard deviation. The study revealed the following: (1) There is a negative correlation between problem-solving skill and negative thinking about the future and anxiety about stressful life events. (2) There is a positive correlation between suicidal ideations and each of the following dimensions: negative thinking about the future, anxiety about stressful life events, and physical manifestations.(3) There is a statistically significant relationship between suicidal ideations and both dimensions of anxiety about stressful life events and psychological manifestations of future anxiety at (0.05 < α). (4) There is a negative correlation between suicidal ideations, the ability to plan to implement the solution to the problem, and the ability to effectively think about solving the problem. (5) There is an average possibility to predict suicidal ideation using problem-solving skill scale as the ratio of the regression coefficient reached (0.643). But there is no predictive ability of suicidal ideation using the future anxiety scale among female students of Taif University. The current study aims to identify some of the factors that would predict the occurrence of suicidal ideations by examining its relations with the variables of problem-solving skill and future anxiety among a sample of (146) of undergraduate females that aged (18 – 25) in Taif University which was collected randomly. To test the hypotheses, the study takes the correlational descriptive method using the Future Anxiety Scale (Al-Mashikhi, 2009), the Suicidal Ideation Scale (Al-Harithi, 2019), and the Problem-Solving Scale (Al-Hariri, 2017). Also, Data was analyzed statistically using Spearman’s rank correlation coefficient, multiple linear regression, means and standard deviation. The study revealed the following: (1) There is a negative correlation between problem-solving skill and negative thinking about the future and anxiety about stressful life events. (2) There is a positive correlation between suicidal ideations and each of the following dimensions: negative thinking about the future, anxiety about stressful life events, and physical manifestations.(3) There is a statistically significant relationship between suicidal ideations and both dimensions of anxiety about stressful life events and psychological manifestations of future anxiety at (0.05 < α). (4) There is a negative correlation between suicidal ideations, the ability to plan to implement the solution to the problem, and the ability to effectively think about solving the problem. (5) There is an average possibility to predict suicidal ideation using problem-solving skill scale as the ratio of the regression coefficient reached (0.643). But there is no predictive ability of suicidal ideation using the future anxiety scale among female students of Taif University.